Photobiodegradation of phenol using mixed microbial culture and N-S TiO2 under visible light - Nordin, Mohamed Firdaus (2016)
Photobiodegradation is a process of combining two methods of degradation which are photodegradation and biodegradation. In this project, it uses both the light and microorganism (mixed microbial culture) to degrade phenol compound. The kinetic of photodegradation of phenol using N-S TiO2 catalyst under visible light at various dopant concentrations, catalyst loadings and initial phenol concentrations (during photobiodegradation) were investigated. The biodegradation performance (during photobiodegradation) was also evaluated. From the first experiment, the dopant concentration that offers the best result for first order reaction was 1.00% with the apparent rate concstant, kobs of 0.226 h-1 . Meanwhile, the best catalyst loading was 2 g/l with kobs of 0.564 h-1 . For photobiodegradation, the most promising result was obtained at the initial phenol concentration of 25 ppm where complete phenol degradation achieved within six hours of reaction.